Las divergencias socioeconómicas territoriales como alternativa metodológica del ordenamiento territorial en México - Propín Frejomil, E.; Sánchez-Crispín, A.; Casado Izquierdo, J.M. (Geographicalia, 2016)
This paper examines the territorial socio-economic differences arising from the inconsistency between development level and socio-economic potential in each of the Mexican states. To begin with we present the theoretical positions which explain the contribution of Geography with regard to spatial management studies. Then we proceed to look at the basic features of development levels and socio-economic potential of the Mexican states; this is followed by the analysis of their territorial differences. We hope our research findings can contribute to setting up national criteria necessary to support spatial management studies in Mexico.
Keywords: Spatial management; Mexico; integrated socio-economic diagnosis.